2010
DOI: 10.1007/s12253-010-9248-8
|View full text |Cite
|
Sign up to set email alerts
|

CD24 and Galectin-1 Expressions in Gastric Adenocarcinoma and Clinicopathologic Significance

Abstract: CD24 and galectin-1 expression in gastric adenocarcinoma and their clinicopathologic significance remained largely unknown. We aimed to evaluate expressions and staining intensities of CD24 and galectin-1 in gastric adenocarcinoma and to investigate the interrelation with clinicopathologic parameters including survival. 93 cases with gastric adenocarcinoma were reevaluated histopathologically and immunohistochemistry was performed with antibodies against CD24 and galectin-1. Staining intensities of both marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
2
26
0
2
Order By: Relevance
“…Although CD24 is known to be overexpressed in gastric adenocarcinoma (4) and gastric cancer stem cells (39), previous immunohistochemical studies have not demonstrated expression in normal human gastric epithelium (6).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Although CD24 is known to be overexpressed in gastric adenocarcinoma (4) and gastric cancer stem cells (39), previous immunohistochemical studies have not demonstrated expression in normal human gastric epithelium (6).…”
mentioning
confidence: 93%
“…CD24 IS A HEAVILY GLYCOSYLATED glycosyl phosphatidylinositollinked glycoprotein, and increased expression of CD24 has been associated with poor prognosis (4,6,37), tumor progression (1,14), and metastasis in several gastrointestinal (GI) cancers. The function of CD24 in the GI tract, however, remains largely unknown, although its roles in regulating immune cell apoptosis (5,33) and differentiation (16,17) as well as cell migration (27) have been well characterized in other tissues.…”
mentioning
confidence: 99%
“…However, Okada et al [23] demonstrated that reduced galectin-3 expression was associated with lymph node metastasis, advanced stage, and tumor differentiation in GC. It was reported that galectin-1 staining intensity in tumor-associated stromal cells was associated with stage and lymph node metastasis [24]. In regard to galectin-2, Takaishi and Wang [21] confirmed reduced expression of the galectin-2 gene in GC lesions in Helicobacter-infected mice.…”
Section: Discussionmentioning
confidence: 85%
“…emlőtumor sztróma sejtekben [105,115,116], tumor endotéliumban [117]. Az irodalmi adatok szerint a Gal-1 mennyisége a tumor metasztatikus hajlamával és a betegség rossz prognózisával jelentős korrelációt mutat [102].…”
Section: A a Galektin-1 Tumor Fejlődésben Betöltött Szerepeunclassified
“…Az emlő tumorral asszociált sztróma sejtekben termelődő Gal-1 szintje egyenesen arányos a tumor invazivitásával és a nyirokcsomó áttétek gyakoriságával [105]. A saját nem közölt eredményeink és mások adatai [105,115,116] …”
Section: Diszkusszióunclassified